Use of information technology in micro and small family business in Cachoeira-BA (Revista Brasileira de Contabilidade e Gestão, 2016)
This study aims to analyze the use of Technology, of Information Technology in micro and small family businesses Cachoeira - BA compared to the national average, identifying the factors of resistance or not to adopt Information Technology, so understanding the process of using in companies. This work was the basis of data obtained from field research, through questionnaires, observations, and using the survey data conducted by the Brazilian Internet Steering Committee, for proper comparisons to be analyzed. The sample of firms was obtained by simple random sampling without replacement, with an initial sample provided twenty- six companies. We propose an analysis of the use and ownership that the Micro and Small Enterprise family of Cachoeira, Bahia do information technology, offering subsidies for discussion about the current situation of the city and why it might not be adopted or no longer tools Information Technology.
Keywords: information technology; micro and small enterprise; family business